Impaired praxis in gesture imitation by deaf children with autism spectrum disorder. (December 2017) - Shield, Aaron; Knapke, Krista; Henry, Morgan; Srinivasan, Sudha; Bhat, Anjana
Background and aims: Praxis, the ability to plan and execute a series of gestures or motor sequences, is impaired in individuals with autism spectrum disorder. In this paper, we present the first study of praxis during a gesture imitation task in a unique population of children with autism spectrum disorder: deaf children who have been exposed to American Sign Language from birth by their Deaf parents. Lifelong exposure to sign language in deaf individuals entails practice with gesture imitation. We ask if deaf, signing children with autism spectrum disorder present with praxis impairments similar to those reported in the literature for hearing children with autism spectrum disorder not exposed to sign. Methods: Thirty deaf children of Deaf parents (16 typically developing and 14 with autism spectrum disorder), matched for chronological and mental age, were tested on a simple gesture imitation task. Children were asked to imitate 24 gestures performed by an adult model on a laptop computer that varied along dimensions of movement type (16 trials) and palm orientation direction (eight trials). Data were coded for nine praxis parameters (five formation parameters and four manner parameters) and three timing measures. Results: Results showed that the deaf children with autism spectrum disorder produced more errors than the typically developing deaf children on six of the nine praxis dimensions (hand orientation, final orientation, modulation, directness, pace, and overflow) and were more impaired on manner parameters than formation parameters, suggesting underlying deficits in motor control/coordination leading to dyspraxia. Praxis scores were strongly related to severity of autism spectrum disorder symptoms and receptive sign language scores. Conclusions: We thus find evidence that praxis is impaired in deaf, signing children with autism spectrum disorder, despite lifelong exposure to a gestural language and extensive practice with gesture imitation. Implications: Our findings suggest that interventions targeted toward enhancing praxis and coordination of finger and hand movements could help facilitate language development in children with autism spectrum disorder.